2011
DOI: 10.3846/16111699.2011.599409
|View full text |Cite
|
Sign up to set email alerts
|

How Entrepreneurial Characteristics Influence Company Creation: A Cross-National Study of 22 Countriestested With Panel Data Methodology / Verslumo Charakteristikų Įtaka Įmonės Kūrimui: Studijos, Atliktos 22 Valstybėse, Rezultatų Pristatymas

Abstract: This study analyzes, from a multicountry perspective, the in uence of the sociodemographic pro les of nascent and new entrepreneurs on their behavior. The panel data-based research approach combines temporal series and cross-sectional data to assess entrepreneurial activities across 22 countries with varying income levels. The results show that entrepreneurs' characteristics in uence entrepreneurial behavior signi cantly and positively, in the following order: previous experience of the founder, age, and educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…With respect to the need for targeted entrepreneurship education and training, we found that although close to 90% of the undergraduate students in our sample expressed interest in starting a new venture, less than 10% had undergone any formal training or developed the requisite skills to engage in entrepreneurial activities. These results provide evidence in support of the need to initiate or improve entrepreneurship education and training (Grüner, Neuberger 2006), particularly for women (Alvarez-Herranz et al 2011). As Kourilsky and Walstad (1998) suggested in their study of female US youth, targeted entrepreneurship training is particularly needed in order to enhance young women's confidence as entrepreneurs and managers, as prior research has indicated that women generally demonstrate lower confidence in their abilities and exhibit lower self-efficacy.…”
Section: Implications and Conclusionmentioning
confidence: 54%
“…With respect to the need for targeted entrepreneurship education and training, we found that although close to 90% of the undergraduate students in our sample expressed interest in starting a new venture, less than 10% had undergone any formal training or developed the requisite skills to engage in entrepreneurial activities. These results provide evidence in support of the need to initiate or improve entrepreneurship education and training (Grüner, Neuberger 2006), particularly for women (Alvarez-Herranz et al 2011). As Kourilsky and Walstad (1998) suggested in their study of female US youth, targeted entrepreneurship training is particularly needed in order to enhance young women's confidence as entrepreneurs and managers, as prior research has indicated that women generally demonstrate lower confidence in their abilities and exhibit lower self-efficacy.…”
Section: Implications and Conclusionmentioning
confidence: 54%
“…Entrepreneurs' characteristics influence the entrepreneurial behavior significantly (Álvarez-Herranz et al, 2011). Some entrepreneurs engage in companies' inventive activities, which enhances firms' absorptive capacity (Mueller et al, 2020) and spurs firms' survival and growth (Haeussler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another demographic variable that can potentially influence both probabilities of engagement into gig and sharing economy initiatives and development of entrepreneurial intentions is individual age (Levesque and Minniti, 2011). As such, younger people might be more inclined to come up with the decision to engage in entrepreneurship as they usually are more enthusiastic, energetic and dynamic (Alvarez-Herranz et al, 2011;Kallas and Parts, 2020) qualities that are intrinsic to those who chose entrepreneurial career path. Moreover, they have a lower opportunity cost of time, higher present value of future income streams and more extensive time horizon of planning (Gielnik et al, 2014;Levesque and Minniti, 2011), as well as greater flexibility in terms of potential careers choice.…”
Section: Demographic Characteristicsmentioning
confidence: 99%